2016
DOI: 10.3892/etm.2016.3591
|View full text |Cite
|
Sign up to set email alerts
|

Decorin reduces hypertrophic scarring through inhibition of the TGF-β1/Smad signaling pathway in a rat osteomyelitis model

Abstract: Chronic osteomyelitis is a bone infection that results in hypertrophic scarring of the soft tissue surrounding the infected bone. This scarring can create functional problems and its treatment is challenging. The aim of the present study was to evaluate the efficacy of decorin in treating scar formation in osteomyelitis and the underlying mechanism of its action. A rat osteomyelitis model was used, and animals were divided into three groups, as follows: Group A (control), group B (osteomyelitis model) and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…There are three approaches or classes of drugs to inhibit biological targets 39 . These include small molecular weight chemical compound (SMOL) inhibitors 20 , 45 , 46 , biologics (antibodies or other proteins that induce conformational changes to alter target function or favor the transition from active to latent forms) 3 , 5 , 47 50 and nucleic acids (acting through RNA interference mechanisms) 40 , 51 . Regardless of drug class, the route of administration is a critical factor in designing molecular therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…There are three approaches or classes of drugs to inhibit biological targets 39 . These include small molecular weight chemical compound (SMOL) inhibitors 20 , 45 , 46 , biologics (antibodies or other proteins that induce conformational changes to alter target function or favor the transition from active to latent forms) 3 , 5 , 47 50 and nucleic acids (acting through RNA interference mechanisms) 40 , 51 . Regardless of drug class, the route of administration is a critical factor in designing molecular therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus overexpression of IL-12 and decorin have demonstrated potent antitumor effects in a weakly immunogenic murine model of breast cancer (Oh et al, 2017a). Along similar lines, adenoviral overexpression of decorin and Granulocyte Macrophage Colony Stimulating Factor has shown anti-tumor potential in a model of murine colorectal cancer (Liu et al, 2017) (Wang et al, 2016). Shen and coworkers engineered a recombinant decorin fusion protein with an extended C-terminus comprised of a vascular homing peptide that recognizes inflamed blood vessels and penetrates deep into the vessel wall, known as CAR.…”
Section: Decorinmentioning
confidence: 94%
“…Ahmed et al (2014) showed that treatment of acute and chronic dorsal funicular spinal cord lesions (DFL) in adult rats with decorin resulted in a reduction in wound cavity area, suppression of inflammatory fibrosis, and dissolution of mature scars due to decorin's fibrolytic activity and neutralization of TGF-b1/2. In an independent study, decorin treatment reduced hypertrophic scarring through inhibition of the TGF-b1/Smad signaling pathway in a rat osteomyelitis model (Wang et al, 2016).…”
Section: Decorinmentioning
confidence: 97%
See 1 more Smart Citation
“…The proteolytic modulation of collagen function is regulated my miRNAs miR-10a and miR-181c, which affect this process in hypertrophic scar fibroblasts by targeting PAI-1 and uPA and increasing MMP-1 levels [353]. Hypertrophic scars exhibit a lower expression of the PG decorin compared to healthy tissue [354] and it has been shown that decorin reduces hypertrophic scarring by modulating TGF-β functions [355,356]. Notably, miR-181b, a miRNA that is upregulated in hypertrophic scars, was shown to target decorin.…”
Section: Microrna -Ecm Interactions In Wound Healingmentioning
confidence: 99%